(untitled) (Journal of Plant Disease Sciences, 2024)
In India, Maharashtra, Karnataka, Andhra Pradesh, Madhya Pradesh, Gujarat and Tamil Nadu are major sorghum growing states. In Maharashtra sorghum crop is cultivated for grain and fodder purpose. Among the several sorghum diseases occurring in various parts of Maharashtra, majority of them are reported to be seed borne. The most destructive sorghum diseases reported are fungal diseases. Grain mold fungi of hybrid varieties of sorghum at their maturity, which is coincide with rain in the September-October months is important. Association of fungal flora in 28 sorghum hybrid/varieties assessed at three different stages of crop tested by rolled paper towel method and results revealed that association of fungal flora varied at different stages in respective hybrid /varieties. Highest association of Fusarium spp. and Curvularia spp. observed in respective hybrid/variety at maturity stages. At crop maturity stage results revealed that association of total moldy fungi spp. (46.50 to 91.00 %).